Bovine Lactoferrin Protects Dextran Sulfate Sodium Salt Mice Against Inflammation and Impairment of Colonic Epithelial Barrier by Regulating Gut Microbial Structure and Metabolites - Wang, Shalong; Zhou, Jingyu; Xiao, Da; Shu, Guoshun; Gu, Li (Frontiers in Nutrition, 2021)
Background: Colitis may lead to colon cancer. Bovine lactoferrin (BL) is a multifunctional protein that could regulate the intestinal flora and has anti-inflammatory effects. The aim of this study was to investigate the therapeutic effect of BL on colitis. Methods: Dextran sulfate sodium salt (DSS) was utilized to establish a mouse model of colitis. BL was administered to treat DSS mice. The weight of the mice, the activity and fecal status of the mice were recorded every day. Disease activity index was calculated. After the mice were euthanized, the colon length was measured. Hematoxylin-eosin staining was used to observe the pathological changes of the colon and histological activity index was calculated. The MPO activity of colon tissue was measured. Western blot and immunohistochemistry were used to detect the expression of Claudin-1, Occludin and ZO-1. The expression of IL-1β, IL-6, IL-10, TNF-α and TGF-β in colon tissue were detected by ELISA. The protein expression of MUC2, Reg3γ, β-defensin (HBD-2) and cAMP were detected by IF. The 16s rDNA sequencing determined the type and structure of intestinal flora. LC-MS/MS measured the metabolites of the intestinal flora. Results: Compared with the DSS group, the mice’s weight in the BL group were higher and the length of the colon were longer. At fourteenth day, MPO activity was higher in BL group. Compared with the DSS group, the expression of Claudin-1, Occludin and ZO-1 in the colon were up-regulated in BL group. The expression of IL-1β, IL-6 and TNF-α were lower. The expression of IL-10 and TGF-β were higher. IF showed that the expression of MUC2 and β-defensin (HBD-2) were down-regulated, and the expression of Reg3γ and cAMP were up-regulated. The 16s rDNA sequencing results showed that the alpha diversity and beta diversity was notably changed in DSS mice treated with BL. Metabolomics results showed BL changed purine metabolism in DSS mice. Conclusion: BL alleviated colitis in mice by improving the inflammatory response and the structure of the colon barrier in the colon. BL changed the composition and metabolites of the intestinal flora. Thus, BL might be an effective nutritional supplement for colitis treatment.